The investigation of a ride quality of nonlinear half-car model - Darsivan, Fadly Jashi (IOP Science, 2016)
The paper discusses the ride quality response of a half car model when a bilinear model and a power law model were implemented in the suspension of half car vehicle. The models were subjected to a step and double pothole disturbances. The nonlinearity of the model is contributed by the power law damper models which are located both at the front and at the rear of the vehicle. Passenger car dampers were initially tested on the damper test bench where the dynamic characteristics were obtained. From the experimental results it clearly showed that the automotive damper behaves nonlinearly. From the force-velocity graphs a backbone model was then developed and plot. Based on this graph two types of non-parametric model namely the bilinear model and power law model were then obtained through the Lavenberg-Marquardt curve fitting algorithm (LMA) method. From the multibody system simulations they clearly showed that the bounce and pitch responses of the bilinear damper model illustrates an overestimations of responses compared to the nonlinear damper model which may lead to a less accurate representation of a realistic damper.